Azaallyl-derived ring formation via redox coupling in first row transition metals. (15th January 2019) - Hulley, Elliott B.; Heins, Spencer P.; Wolczanski, Peter T.; Lancaster, Kyle M.; Lobkovsky, Emil B.
Graphical abstract: The reductive coupling of a chelated diimine ligand, Me2 C(CHNCH2 (2-py))2 (dmp(PM)2 ), by (TMEDA)TiCl2 afforded a Ti(IV) cyclopropanated species, Me2 c Pr( cis -2, 3-NCH2 (2-py)2 TiCl2 (1 ), while di-azaallyl precursors were used to generate 7-membered ring chelates [{DBM(PI − )(PI 2− )}Cr III ]2 (4 ) and [{DBM(PI)(PI′)}Fe]2 (5 ). Abstract: The reductive coupling of a chelated diimine ligand, Me2 C(CHNCH2 (2-py))2 (dmp(PM)2 ), by (TMEDA)TiCl2 afforded a Ti(IV) species containing a cyclopropane ring, Me2 c Pr( cis -2, 3-NCH2 (2-py))2 TiCl2 (1 ). Dimeric [{Me2 C(CH2 NCH(2-py)(CH2 (µ-N)CH2 (2-py)}Mg]2 (3 ) was generated in the magnesium reduction of Me2 C(CH2 NCH(2-py))2 (dmp(PI)2 ) as its reduction incurred HAT. A di-azaallyl precursor was used to generate 7-membered ring chelates [{DBM(PI − )(PI 2− )}Cr III ]2 (4 ) and [{DBM(PI)(PI′)}Fe]2 (5 ). Structural studies of1, 3 and4 are included, as are electronic assessments of the reductive coupling to afford1, and the paramagnetism of3 .